MODERN ASPECTS OF PATHOGENESIS OF CHILDHOOD RHINOSINUSITIS - Burxanov , Улугбек; Khushvakova , Нилуфар (International Journal of Scientific Pediatrics, 2024)
The relevance of studying the pathogenesis of childhood rhinosinusitis is highlighted in modern medical practice. This abstract is a literature review highlighting modern aspects of this problem. Rhinosinusitis, although a common disease in children, still causes difficulties in understanding its pathogenesis. The review includes consideration of the mechanisms of development of rhinosinusitis in children, including the influence of infections, allergic reactions, anatomical features and immunological factors. Particular attention is paid to the role of the nasopharyngeal microbiota in the development and progression of rhinosinusitis in children. Modern methods of diagnosis and treatment are also discussed, including the use of antibiotics, antiviral drugs, glucocorticosteroids and surgical interventions. This literature review is a valuable source of information for pediatricians, otolaryngologists and anyone interested in studying the problem of rhinosinusitis in children. Understanding the modern aspects of the pathogenesis of this disease will allow us to develop more effective strategies for diagnosis, treatment and prevention, which ultimately helps improve the quality of life of children and reduce medical costs.